1998
DOI: 10.1021/jp980846d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Kinetics of the Hydrogen Abstraction from Methanol. 2. Reaction of Methanol with Chlorine and Bromine Atoms

Abstract: Ab initio calculations at different levels of theory and using several basis sets have been performed for the title two-channel hydrogen-abstraction reactions CH3OH + Cl and Br. These calculations have shown that, similar to CH3OH + F, both reactions proceed via formation of intermediate complexes. Rate constant calculations for this type of reactions have been performed using the equations developed in Jodkowski, J. T.; Rayez, M.-T.; Rayez, J.-C.; Berces, T.; Sandor, D. J. Phys. Chem. 1998, 102, xxxx. The ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
55
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 32 publications
13
55
0
Order By: Relevance
“…The inclusion of the data of on Cl+CH 3 OD is justified considering the strong body of evidence showing that the H-abstraction proceeds solely at the CH 2 -group at room temperature (see , Radford et al, 1981and Jodkowski et al, 1998. The relative rate study of Wallington et al (1988) …”
Section: Comments On Preferred Valuesmentioning
confidence: 99%
“…The inclusion of the data of on Cl+CH 3 OD is justified considering the strong body of evidence showing that the H-abstraction proceeds solely at the CH 2 -group at room temperature (see , Radford et al, 1981and Jodkowski et al, 1998. The relative rate study of Wallington et al (1988) …”
Section: Comments On Preferred Valuesmentioning
confidence: 99%
“…The van der Waals wells associated with the encounter complexes are so shallow in the case of the methane and ethane surfaces that they are expected to have no impact upon the dynamics, which should therefore be direct. Calculations of stationary point energies and geometries for the reaction of Cl atoms with methanol demonstrate that reaction proceeds along a minimum energy pathway that incorporates lower energy preand post-transition state intermediate complexes, 1,23 bound by Ϫ4.64 and Ϫ9.64 kcal mol Ϫ1 , respectively, relative to the reagent energies. The differential cross sections reported by Ahmed et al 24 from crossed molecular beams and velocity map imaging experiments showed scattering that is predominantly in the backward/sideways direction, suggesting direct ͑despite the potential wells͒ rebound dynamics, but recent experiments from Kitsopoulos and co-workers demonstrate that there is also a strong forward scattered component.…”
Section: Introductionmentioning
confidence: 99%
“…All computational effort is then related to calculating the sum of the states, W ( E , J ) This calculation depends on the level at which the conservation of angular momentum is considered and is discussed in detail in Refs. [21, 22]. …”
Section: Resultsmentioning
confidence: 99%
“…The results of direct calculations [13, 2022] show that the dominant contribution to the rate constant is given by states with energy E not higher than V TSx  + 3RT. In the case of a sizable (compared with RT) energy barrier V TSx , the value of the product of the microcanonical branching fractions at an energy slightly higher than V TSx becomes close to unity and the TST rate constant k TST is then a good approximation of the exact rate coefficient, especially at ambient temperatures [13, 2022].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation